Role of Continuous Versus Alternate Regime of Thromboprophylaxis in Obstetric Outcome in Bad Obstetric History (BOH) - Malik, Rubina; Alam, Kinza; Nafisa, Asma (Journal of Rawalpindi Medical College, 2025)
Objective: To compare the frequency of live births in patients with BOH taking LMWH daily versus alternate days. Methods: This was a randomised controlled trial, conducted at the Department of Obstetrics and Gynaecology, at POF Hospital, Wah, from 1st of January to 31st of December 2024. This study included 122 women aged 30-45 years with a history of adverse obstetric outcomes. Participants were randomly assigned to receive 40 mg low molecular weight heparin (LMWH) either daily (Group A Control) or on alternate days (Group B Experimental) starting in first trimester at enrolment visit when fetal cardiac activity becomes positive, with follow-ups assessing compliance, symptoms, and fetal well-being through history and ultrasound. Live birth was the primary outcome. Data analysis was performed using SPSS v. 22, with p-values <0.05 considered statistically significant. Results: The mean age was 34.90 ± 2.56 years, and the mean gestational age at enrolment was 9.95 ± 1.14 weeks. Among them, 46.7% underwent Spontaneous vaginal delivery, 39.3% Cesarean section, and 13.9% Evacuation and curettage, with 76.2% resulting in live births and 27.9% of newborns requiring Neonatal intensive care admission. No significant differences were observed between groups in terms of age, gestational age, mode of delivery, live birth frequency (p = 0.832), or Intrauterine death rates (p = 0.543). However, Neonatal intensive care unit admissions were significantly higher in the control group (p = 0.043). Conclusion: The study found no significant difference between the two groups in terms of live births. However, neonatal intensive care unit admissions were significantly higher in the women receiving a daily low molecular weight heparin dose.